2017
DOI: 10.1186/s40634-017-0112-6
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus as an adjunct to autologous minced muscle grafts for the repair of a volumetric muscle loss injury

Abstract: BackgroundVolumetric muscle loss (VML) following extremity orthopaedic trauma or surgery results in chronic functional deficits and disability. A current translational approach to address the devastating functional limitations due to VML injury is the use of an autologous minced muscle graft (~1 mm3 pieces of muscle tissue) replacement into the injured defect area, although limitations related to donor site morbidity are still unaddressed. This study was designed to explore adjunct pharmacological immunomodula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Therapeutic modalities that incorporate immunomodulatory elements 13 may promote a more favorable environment for subsequent regenerative therapies, by removing debris and emitting soluble factors that recruit and support regenerative progenitors. For example, Corona et al 14 administered Tacrolimus, a calcineurin phosphatase inhibitor that reduces macrophage and dendritic cell activity and inhibits interleukin-2 (IL-2) mediated activation of T lymphocytes, in combination with MMGs. Administration of systemic Tacrolimus with MMGs reduced the functional deficit by about one third compared to MMGs alone.…”
mentioning
confidence: 99%
“…Therapeutic modalities that incorporate immunomodulatory elements 13 may promote a more favorable environment for subsequent regenerative therapies, by removing debris and emitting soluble factors that recruit and support regenerative progenitors. For example, Corona et al 14 administered Tacrolimus, a calcineurin phosphatase inhibitor that reduces macrophage and dendritic cell activity and inhibits interleukin-2 (IL-2) mediated activation of T lymphocytes, in combination with MMGs. Administration of systemic Tacrolimus with MMGs reduced the functional deficit by about one third compared to MMGs alone.…”
mentioning
confidence: 99%
“…In a subsequent study, when FK-506 was injected i.p. and VML defect was treated with autologous minced muscle grafts in a porcine model, muscle regeneration and function was enhanced [24]. Taken together, these studies suggest that a combination of regenerative and immunomodulatory therapy is essential for functional muscle regeneration.…”
Section: Introductionmentioning
confidence: 77%
“…Dendritic cells have been detected as early as 24 hours after muscle injury [69,70]. While continuous administration of FK-506 has been done in VML models [23,24], others have reported that a single local application of FK-506 at the time of repair can support functional nerve regeneration 2-3 months after injury [71,72]. Future studies may investigate the impact of sustained-release FK-506 on VML injury to determine if a short-term administration is adequate.…”
Section: Sponge Treatment Also Resulted In Significant Upregulation Omentioning
confidence: 99%
“…Hence, in addition to topographical guidance, tissue engineered scaffolds must be myo-conductive, promote angiogenesis through either pre-vascularization or incorporation of vasculogenic accelerant, have immunomodulatory effect as well as facilitate reinnervation to overcome the pathophysiology of VML and achieve functional restoration. Direct administration of anti-inflammatory agents can reduce fibrosis but has been shown to hinder muscle regeneration 25,26 . Acellular scaffolds cannot address such multidimensional challenges and reinforces the necessity of incorporating multiple cell types in a scaffold 18 .…”
Section: Introductionmentioning
confidence: 99%